Getting Back on Track: Meanings of Recovery After Critical Illness Caused by COVID-19 - Päivi Juuso PhD, PHN, RN; Åsa Engström PhD, CCN, RN; Ulrica Strömbäck PhD, CCN, RN; Maria Andersson PhD, CCN, RN; Anna Nordin PhD, CCN, RN (SAGE Publishing, 2024)
Introduction Being critically ill in need of intensive care, lead to a challenging way back after survival, so also for survivors of COVID-19. The process to recovery can be long. Objectives The aim of our qualitative study was to elucidate meanings of recovery for people who were once critically ill with COVID-19. Method We conducted qualitative individual interviews with 13 individuals who had been critically ill with COVID-19, following a narrative approach. The data collected from the interviews, were analyzed according to phenomenological hermeneutic interpretation. Results The participants, although feeling alone in the process of recovery, had willpower to return to normal life but struggled to keep pace with others. They strived for balance in everyday life and to regain strength despite being exhausted after having COVID-19. The participants were grateful for their survival but displayed a need to understand what had happened. They longed for social contact, expressed feelings of abandonment, and wished for follow-up dialogues with healthcare professionals to better understand their situation. However, because support from healthcare was insufficient, the participants ultimately needed to develop their own strategies to cope with their questions, fears, and weakness. Conclusion Meanings of recovery for people once critically ill with COVID-19, is to strive for balance in everyday life. In their recovery process, healthcare professionals should seek to understand what the illness means for the ill person, and in mutual understanding support them based on their needs.